Creating Sustainable Operational Excellence in Pharma Manufacturing. - HAIGNEY, SUSAN (Pharmaceutical Technology)
The article focuses on how pharmaceutical companies are integrating sustainability into early drug development to create greener manufacturing processes. Industry experts highlight that the greatest environmental impacts arise from active pharmaceutical ingredient (API) synthesis, chemical operations, and process design, emphasizing the importance of green chemistry, water stewardship, waste reduction, and energy efficiency from the outset. Strategies include adopting continuous processing, biocatalysis, renewable energy, and purpose-built facilities, alongside digital tools for improved yield and reduced waste. Sustainability is increasingly becoming a core metric alongside speed and quality, influencing regulatory expectations, partner selection, and competitive positioning within the pharmaceutical industry.